Răspunsuri

2014-01-28T14:39:23+02:00
A) Notam S = x+y si P = x·y. Stiind ca x² + y² = S² - 2P => 

     5S² -11P = 29  /·2
     7S² -22P = 43

10S² -22P = 58
  7S² -22P = 43  (-) => 3S² = 15 => S² = 5 => S = +√5 sau S = -√5  =>
 => 5· 5 - 11P = 29 => 25 - 11P = 29 => 11P = -4 => P= - 4/11

Deci x + y = √5          sau  x + y = -√5              si calculam x si y.
          x · y = -4/11               x · y = -4/11

b) Avem: P + S = 7   /·3         3P + 3S = 21
                 P - 3S = -9    <=>    P - 3S = -9  (+)  => 4P = 12 => P =3 => S=4 =>
  => x + y = 4           x = 4-y
        x · y = 3   <=>  (4-y) · y = 3 => 4y - y² = 3 => y² - 4y +3 = 0 
                          Δ = 16 - 12 = 4 => y1 = (4 + 2):2 = 3 => x1 = 1
                                                           y2 = (4 - 2):2 = 1 => x2 = 3
         Deci ( x ; y ) ∈ { ( 1 ; 3 ); ( 3 ; 1 ) }
                                                               
1 5 1